Balancing Work-Family Roles: The Experiences of Solo Parent School Administrators - Encila, Mary Grace F.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
The rising educational attainment for women and economic uncertainty gave rise to high maternal employment rates and the global labour force participation of women. Often working mothers, are put into the complexities of work and family life, resulting in stress and perplexity of values and priority. The phenomenological paper intends to explore the day-to-day life experiences and the balance of work-home life of school administrators involved in solo-parenting in the Diocesan Schools of Negros Occidental, Philippines. The data were collected using an in-depth interview from four school administrators chosen through purposive sampling. Thematic analysis following Lichtman’s three Cs: coding, categorizing, and conceptualizing was used to analyse the data. The findings show that playing the role of an administrator and being a solo parent at the same time is both a challenging and rewarding task. School administrators employed various coping mechanisms such as seeking external help and involving in productive activities to manage daily stressors. In the absence of their spouse, time management is essential, and spending quality time with children is always a priority. The findings may provide baseline data for designing and implementing stress management programs to ensure the balance of work-family roles.